Learning Social Arithmetic of Low-Ability Student through the Context of Snacks and Money - Risty Mustika Hardini; Rully Charitas Indra Prahmana; Irwan Akib; Masitah Shahrill (Universitas Muhammadiyah Surakarta, 2022)
Low-ability students are evidenced to have difficulties in understanding the concept of abstraction in mathematics, such as social arithmetic problems. It is because low-ability students have an IQ below the average of 70 to 90. Most teachers find it challenging to discover what kind of learning approaches that may be suitable for improving their mathematical understanding. An alternative approach that can be used to improve the understanding of low-ability students is the Indonesian Realistic Mathematics Education (IRME) approach by using real contexts as a starting point for learning to make it easier for students to study the abstract material. This study aims to determine the learning process and the role of IRME in improving low-ability student’s mathematical cognitive abilities regarding the concept of social arithmetic. This study used the Single Subject Research (SSR) method with a single subject, and a seventh-grade student at one of the Junior High Schools in Depok, Yogyakarta. The research data collected in this study are audio and video recordings, photos, and student worksheets. The data collected was then analyzed using in and between analysis with A-B research design. The results showed that the IRME approach with snack and money con-texts could improve a low-ability student’s mathematical understanding of the social arithmetic concept. This context could be a starting point for teachers in teaching social arithmetic problems and be a reference for finding other contexts that can make mathematics learning more easy and joyful for low-ability students.